Responses of commonly cultivated tomato cultivars in Nepal to bacterial speck - LAMICHHANE, Jay Ram; BALESTRA, Giorgio; VARVARO, Leonardo (Phytopathologia Mediterranea, 2011)
Ten predominantly cultivated cultivars of tomato (Solanum lycopersicum L.) in Nepal were tested in the plastic tunnel and in the field for their susceptibility to Pseudomonas syringae pv. tomato, the causal agent of bacterial speck. Each cultivar was artificially inoculated with P. s. pv. tomato, by means of a leaf spray method both in the tunnel and in the field. Among the tested cultivars four out of ten were local cultivars and the remaining cultivars were hybrids. The genotypes exhibited a large amount of variation in response to the bacterial infection, with disease severity index (DSI) ratings from 1.80 to 4.25 in the field and from 1.10 to 4.20 in the tunnel. The cultivars Thims 16, C.L. and Spectra 737 were the less susceptible in the field, with DSI values of 1.80, 2.05 and 2.25, respectively; while in the tunnel all the local cultivars (C.L., Panjabi, B.L. and Lapsi Gede) showed a very low level of susceptibility, with respective DSI values of 1.10, 1.20, 1.65 and 2.30. In the field, the most susceptible was the cultivar Lapsi Gede (DSI=4.25) and in the tunnel it was represented by the cultivar NS-719 (DSI= 4.20). <!–st1\:*behavior:url(#ieooui) –>